Assessing The Severity of Oropharyngeal Dysphagia and its Relation to Quality of Life Status in Head and Neck Cancer Patients After Undergoing Chemoradiotherapy in DR Sardjito Public Hospital, Yogyakarta, Indonesia: A Cross Sectional Prospective Study - Anisa Haqul Khoiria; Agus Surono; Camelia Herdini (Advances In Social Humanities Research, 2026)
Head and neck cancer treatment frequently causes oropharyngeal dysphagia, which may impair nutritional status, psychological well-being, social functioning, and overall quality of life. This study aimed to assess dysphagia severity and swallowing-related quality of life, compare changes in these outcomes during early follow-up, and determine the relationship between dysphagia severity and quality of life among patients after chemoradiotherapy. A prospective observational study was conducted among 60 patients with head and neck cancer at the ENT Outpatient Clinic of Dr. Sardjito General Hospital, Yogyakarta. Oropharyngeal dysphagia was evaluated using the Gugging Swallowing Screen, while quality of life was measured using the Indonesian version of the Swallowing Quality of Life questionnaire during the first and 12th weeks after treatment. Data were analyzed using the Kruskal–Wallis, Gamma correlation, and Friedman tests. Dysphagia severity was significantly associated with quality of life at the first week (r = 0.729; p < 0.001) and the 12th week (r = 0.827; p < 0.001). However, dysphagia severity (p = 0.782) and quality of life (p = 1.000) did not change significantly between assessments. Delayed swallowing was the predominant symptom, whereas burden and eating desire were the most affected quality-of-life domains. In conclusion, persistent dysphagia was strongly associated with poorer quality of life, emphasizing the need for early screening, multidisciplinary management, and continuous swallowing rehabilitation.